Advance Care Planning Video Intervention Among Long-Stay Nursing Home Residents: A Pragmatic Cluster Randomized Clinical Trial - Mitchell, Susan L; Volandes, Angelo E; Gutman, Roee; Gozalo, Pedro L; Ogarek, Jessica A; Loomer, Lacey; McCreedy, Ellen M; Zhai, Ruoshui; Mor, Vincent (JAMA internal medicine, 2020)
Standardized, evidenced-based approaches to conducting advance care planning (ACP) in nursing homes are lacking. To test the effect of an ACP video program on hospital transfers, burdensome treatments, and hospice enrollment among long-stay nursing home residents with and without advanced illness. The Pragmatic Trial of Video Education in Nursing Homes was a pragmatic cluster randomized clinical trial conducted between February 1, 2016, and May 31, 2019, at 360 nursing homes (119 intervention and 241 control) in 32 states owned by 2 for-profit corporations. Participants included 4171 long-stay residents with advanced dementia or cardiopulmonary disease (hereafter referred to as advanced illness) in the intervention group and 8308 long-stay residents with advanced illness in the control group, 5764 long-stay residents without advanced illness in the intervention group, and 11 773 long-stay residents without advanced illness in the control group. Analyses followed the intention-to-treat principle. Five 6- to 10-minute ACP videos were made available on tablet computers or online. Designated champions (mostly social workers) in intervention facilities were instructed to offer residents (or their proxies) the opportunity to view a video(s) on admission and every 6 months. Control facilities used usual ACP practices. Twelve-month outcomes were measured for each resident. The primary outcome was hospital transfers per 1000 person-days alive in the advanced illness cohort. Secondary outcomes included the proportion of residents with or without advanced illness experiencing 1 or more hospital transfer, 1 or more burdensome treatment, and hospice enrollment. To monitor fidelity, champions completed reports in the electronic record whenever they offered to show residents a video. The study included 4171 long-stay residents with advanced illness in the intervention group (2970 women [71.2%]; mean [SD] age, 83.6 [9.1] years), and 8308 long-stay residents with advanced illness in the control group (5857 women [70.5%]; mean [SD] age, 83.6 [8.9] years), 5764 long-stay residents without advanced illness in the intervention group (3692 women [64.1%]; mean [SD] age, 81.5 [9.2] years), and 11 773 long-stay residents without advanced illness in the control group (7467 women [63.4%]; mean [SD] age, 81.3 [9.2] years). There was no significant reduction in hospital transfers per 1000 person-days alive in the intervention vs control groups (rate [SE], 3.7 [0.2]; 95% CI, 3.4-4.0 vs 3.9 [0.3]; 95% CI, 3.6-4.1; rate difference [SE], -0.2 [0.3]; 95% CI, -0.5 to 0.2). Secondary outcomes did not significantly differ between trial groups among residents with and without advanced illness. Based on champions' reports, 912 of 4171 residents with advanced illness (21.9%) viewed ACP videos. Facility-level rates of showing ACP videos ranged from 0% (14 of 119 facilities [11.8%]) to more than 40% (22 facilities [18.5%]). This study found that an ACP video program was not effective in reducing hospital transfers, decreasing burdensome treatment use, or increasing hospice enrollment among long-stay residents with or without advanced illness. Intervention fidelity was low, highlighting the challenges of implementing new programs in nursing homes. ClinicalTrials.gov Identifier: NCT02612688.